Prepregnancy Diabetes and Offspring Risk of Congenital Heart Disease: A Nationwide Cohort Study. Issue 23 (7th June 2016) - Øyen, Nina; Diaz, Lars J.; Leirgul, Elisabeth; Boyd, Heather A.; Priest, James; Mathiesen, Elisabeth R.; Quertermous, Thomas; Wohlfahrt, Jan; Melbye, Mads
Abstract : Background—: Maternal diabetes mellitus is associated with an increased risk of offspring congenital heart defects (CHD); however, the causal mechanism is poorly understood. We further investigated this association in a Danish nationwide cohort. Methods and Results—: In a national cohort study, we identified 2 025 727 persons born from 1978 to 2011; among them were 7296 (0.36%) persons exposed to maternal pregestational diabetes mellitus. Pregestational diabetes mellitus was identified by using the National Patient Register and individual-level information on all prescriptions filled in Danish pharmacies. Persons with CHD (n=16 325) were assigned to embryologically related cardiac phenotypes. The CHD prevalence in the offspring of mothers with pregestational diabetes mellitus was 318 per 10 000 live births (n=232) in comparison with a baseline risk of 80 per 10 000; the adjusted relative risk for CHD was 4.00 (95% confidence interval, 3.51–4.53). The association was not modified by year of birth, maternal age at diabetes onset, or diabetes duration, and CHD risks associated with type 1 (insulin-dependent) and type 2 (insulin-independent) diabetes mellitus did not differ significantly. Persons born to women with previous acute diabetes complications had a higher CHD risk than those exposed to maternal diabetes mellitus without complications (relative risk, 7.62; 95% confidence interval, 5.23–10.6, and relative risk, 3.49; 95% confidence interval, 2.91–4.13, respectively; P =0.0004). All specific CHD phenotypes were associated with maternal pregestational diabetes mellitus (relative risk range, 2.74–13.8). Conclusions—: The profoundly increased CHD risk conferred by maternal pregestational diabetes mellitus neither changed over time nor differed by diabetes subtype. The association with acute pregestational diabetes complications was particularly strong, suggesting a role for glucose in the causal pathway.